The given points (-5,-49), (2,-22), and (3,23) satisfy the equation y=9x-4, which means that when x is plugged into the equation, it produces the corresponding y value for each point.
For example, when x=-5, y=9(-5) - 4 = -49, so (-5,-49) satisfies the equation.
Similarly, when x=2, y=9(2) - 4 = -22, so (2,-22) satisfies the equation.
And when x=3, y=9(3) - 4 = 23, so (3,23) satisfies the equation.
Therefore, all three points satisfy the equation and are solutions to y=9x-4.
Why is (-5, -49)(2,-22)(3,23) the solution to y=9x - 4 Explain
2 answers
geez - how many time are you going to ask the same dumb question?